THE STATE OF INTEGRATION IN HIGHER EDUCATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Implementing reforms in developing higher education at the international level in the Republic of Uzbekistan have entered a new phase. In particular, the integration of national higher education into world higher education, raising the level of quality to the international level, organization of higher education based on international educational standards, establishing cooperation with higher education institutions of developed countries are being paid great attention. The rationale of the study is to highlight the process of integrating higher education of the Republic of Uzbekistan into the world higher education area. It is emphasized that internationalization of higher education is an important factor in the integration into the world higher education.